Genetic characteristics of azithromycin-resistant Neisseria gonorrhoeae collected in Hyogo, Japan during 2015–2019. Issue 6 (14th June 2022) - Miura, Makiko; Shigemura, Katsumi; Osawa, Kayo; Nakanishi, Noriko; Nomoto, Ryohei; Onishi, Reo; Yoshida, Hiroyuki; Sawamura, Toru; Fang, Shiuh-Bin; Chiang, Yi-Te; Sung, Shian-ying; Chen, Kuan-cho; et al.
Abstract : Introduction. Azithromycin (AZM) is a therapeutic drug for sexually transmitted infections and is used for Neisseria gonorrhoeae when first- and second-line drugs are not available. Recently, the susceptibility of N. gonorrhoeae against AZM has been decreasing worldwide. Hypothesis/Gap Statement. Azithromycin-resistance (AZM-R) rates among N. gonorrhoeae in Japan are increasing, and the gene mutations and epidemiological characteristics of AZM-R in N. gonorrhoeae have not been fully investigated. Aim. We determined the susceptibility to AZM and its correlation with genetic characteristics of N. gonorrhoeae . Methodology. We investigated the susceptibility to AZM and genetic characteristics of N. gonorrhoeae . Mutations in domain V of the 23S rRNA gene and mtrR were examined in 93 isolates, including 13 AZM-R isolates. Spread and clonality were examined using sequence types (STs) of multi-antigen sequence typing for N. gonorrhoeae (NG-MAST), and whole genome analysis (WGA) to identify single nucleotide polymorphisms. Results. The number of AZM-R isolates increased gradually from 2015 to 2019 in Hyogo ( P =0.008). C2599T mutations in 23S rRNA significantly increased in AZM-R isolates ( P <0.001). NG-MAST ST4207 and ST6762 were frequently detected in AZM-R isolates, and they had higher MICs to AZM from 6 to 24 µg/ml. The phylogenic tree-based WGA showed that all isolates with ST4207 were contained in the same clade, and isolates with ST6762 were divided into two clades, AZM-S isolates and AZM-R isolates, which were different from the cluster containing ST1407. Conclusion. Our study showed yearly increases in AZM-R rates in N. gonorrhoeae . NG-MAST ST4207 and ST6762 were not detected in our previous study in 2015 and were frequently identified in isolates with higher MICs to AZM. WGA confirmed that isolates with these STs are closely related to each other. Continued surveillance is needed to detect the emergence and confirm the spread of NG-MAST ST4207 and ST6762.